An Upper Triassic terrestrial vertebrate assemblage from the forgotten Kocury locality (Poland) with a new aetosaur taxon. Issue 1 (2nd January 2021) - Czepiński, Łukasz; Dróżdż, Dawid; Szczygielski, Tomasz; Tałanda, Mateusz; Pawlak, Wojciech; Lewczuk, Antoni; Rytel, Adam; Sulej, Tomasz
ABSTRACT: Since 1990, several localities within the Keuper (upper Middle to Upper Triassic) strata in southern Poland have yielded remains of numerous terrestrial vertebrate species. Here we report a new Upper Triassic vertebrate assemblage from the rediscovered Kocury locality. An incomplete theropod dinosaur fibula named Velocipes guerichi described in 1932 was found there. The site was then forgotten and not explored until our excavations began in 2012, that yielded material of a lungfish, a proterochersid turtle, and a new typothoracin aetosaur Kocurypelta silvestris gen. et sp. nov. The new taxon is characterized by autapomorphies of the maxilla: an elongated edentulous posterior portion longer than 80% of the posterior maxillary process, a short medial shelf restricted to the posterior portion of the bone, an anteriorly unroofed maxillary accessory cavity, and lack of a distinct groove for choanal recess on the anteromedial surface of the bone. These new finds improve our knowledge on the vertebrate diversity of the Germanic Basin in the Late Triassic, evidencing the presence of yet unrecognized taxa. Additionally, the partial cranial aetosaur material emphasizes the issues with the aetosaurian taxonomy that is focused mostly on the osteoderm morphology.